ANALYZING & PREDICTING STUDENTS’ PERFORMANCES USING MACHINE LEARNING - Atharva M. Wankhede, Suraj M. Jha, Varad R. Patil,; Mr. Pravin V. Shinde, (EPRA International Journal of Research and Development (IJRD), 2022)
Literacy is very critical to economic development as well as individual and community well-being. Effective literacy skills open the doors to more educational & employment opportunities. Moreover, the economic success of any country highly depends on making higher education more affordable and that considers one of the main concerns for any government. Thus, this Machine Learning project is to classify and predict the future academic grades and leadership scores of the students. The ability to predict student performance in education is very significant in educational environments. This will help teachers and professors in school and universities consolidate the student on improving and developing each student’s curriculum record. The main intention is to identify and support the students to score better marks for their betterment.